A rare case of nevus sebaceous of the bilateral labia minora: A case report and review of literature. Issue 10 (12th March 2021) - Wen, Qiao; Zhao, Zhiwei; Yang, Yanlin; Zhao, Fengnian; Wang, Ling; Cheng, Juan; Wu, Jiang; Miao, Yali
Abstract: Rationale: Nevus sebaceous (NS) is a lesion caused by congenital hyperplastic disorder of the sebaceous glands. It commonly noted in the scalp and face and rarely in the trunk, neck, or oral mucosa. We present a rare case of a lesion arising in the genital region. Patient concerns: A 47-year-old woman complained of a gradual increase in the size of her bilateral labia minora over 2 years, which affected her sexual life and caused walking difficulty. She was admitted to the Department of Obstetrics and Gynecology. On physical examination, no ulcer, discharge, and vulval or vaginal bleeding were found. The bilateral inguinal lymph nodes were not palpable, bilateral labia minora were asymmetric, and the right side was evidently bigger than the left. The labia minora had serrated edges and numerous papillae with a maximum diameter of 0.5 cm. The vagina, cervix, and uterus with its attachments were normal. Blood samples tested negative for human immunodeficiency virus, human papilloma virus, hepatitis B virus, and hepatitis C virus. Diagnosis: A diagnosis of NS of the bilateral labia minora was made following histopathological examination of the resected specimen. Intervention: The bilateral labia minora lesions were resected general anesthesia on August 29, 2016. The operation was successful, and intraoperative blood loss was about 10 ml. Outcomes: After 40 months of postoperative follow-up, no recurrence or appearance of other tumors were noted. Lessons: We recommend surgical removal of lesions in the genital area during adolescence or before adulthood. Adolescence may be the best period for surgical intervention owing to a greater risk of malignant change in adulthood. On the other hand, surgical risk should be avoided in children considering the low incidence of malignant transformation.